2001
DOI: 10.1038/nsb0901-756
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: p53 is a nuclear phosphoprotein that regulates cellular fate after genotoxic stress through its role as a transcriptional regulator of genes involved in cell cycle control and apoptosis. The C-terminal region of p53 is known to negatively regulate sequence specific DNA-binding of p53; modifications to the C-terminus relieve this inhibition. Two models have been proposed to explain this latency: (i) an allosteric model in which the C-terminal domain interacts with another domain of p53 or (ii) a competitive mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
109
1
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(114 citation statements)
references
References 38 publications
3
109
1
1
Order By: Relevance
“…The first study showed that RSp53 binds readily to its sequence-specific DNA target without activation, but in the presence of a large excess of non-specific competitor DNA this binding requires activation (Nichols and Matthews, 2001). In the second study, a dimeric p53 protein with an intact C-terminus was also shown to bind to its DNA target in the absence of non-specific competitor DNA, although its binding affinity was lower than that of the C-terminus truncated protein (Ayed et al, 2001). In addition, the NMR spectra of the two dimeric proteins were indistinguishable, suggesting that the 'latent' and 'active' proteins adopt similar conformations in the absence of DNA (Ayed et al, 2001).…”
Section: Discussionmentioning
confidence: 89%
“…The first study showed that RSp53 binds readily to its sequence-specific DNA target without activation, but in the presence of a large excess of non-specific competitor DNA this binding requires activation (Nichols and Matthews, 2001). In the second study, a dimeric p53 protein with an intact C-terminus was also shown to bind to its DNA target in the absence of non-specific competitor DNA, although its binding affinity was lower than that of the C-terminus truncated protein (Ayed et al, 2001). In addition, the NMR spectra of the two dimeric proteins were indistinguishable, suggesting that the 'latent' and 'active' proteins adopt similar conformations in the absence of DNA (Ayed et al, 2001).…”
Section: Discussionmentioning
confidence: 89%
“…Thus, p53 is not 'latent' for p53-SSDB per se, but it appears like being 'latent' with certain types of DNA templates. Further supporting the conclusion, comparative structural analyses revealed that the global conformation of the p53-DBD is largely uninfluenced by the p53-CTD, 13 a finding that undermined a stronghold of the 'p53 latency' concept postulating that p53-CTD inhibits p53-SSDB by conformationally inhibiting the p53-DBD. Finally, the decisive evidence eliciting the impact of the p53-CTD on p53-SSDB under physiological conditions was provided recently in a recent study by McKinney et al 5 demonstrating that deletion of the p53-CTD impairs p53-SSDB and the potential of p53 to activate transcription in vivo.…”
mentioning
confidence: 70%
“…Cell Death and Differentiation (2006) 13,[885][886][887][888][889] Initially, the long known ability of p53 to sense structurally distorted DNA was considered to underlie primarily the interaction of p53 with aberrant sites in damaged DNA that may occur anywhere in the genome and therefore cannot be sequence-dependent. The fact that in vitro, distinct domains of the p53 protein elicit different modes of DNA binding independently from each other seemed to further support the idea that the different modes of p53 DNA binding are functionally unrelated: whereas p53-SSDB is a major function of the p53 core DNA binding domain (p53-DBD), 8 p53 binding to aberrant DNA structures has been firmly associated with the p53 C-terminal domain (p53-CTD), which can bind efficiently different types of aberrant DNA sites in the absence of the p53-DBD.…”
mentioning
confidence: 99%
“…Positive regulation of SSDB by the C-terminus was observed by Gohler et al (2002) in studies of p53 binding to stem loop oligo structures, and by McKinney and Prives (2002), who studied p53 binding to the 66 bp oligo (containing a p53 binding site) when it was locked in a microcircle. The question of the mechanism of p53 latency and the role of the C-terminus has been intensively discussed (Ayed et al, 2001;Yakovleva et al (2001) and references therein). This discussion may soon lead to more complex models involving not only the interactions and conformations of p53, but also the global and local DNA structures, as well as the positive regulation of p53 binding.…”
Section: Effect Of Supercoiling On P53 Dna Sequence-specific Bindingmentioning
confidence: 99%